Consumer Exploitation and Notice Periods - Takeshi Murooka; Marco Schwarz (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
Firms often set long notice periods when consumers cancel a contract, and sometimes do so even when the costs of changing or canceling the contract are small. We investigate a model in which a firm offers a contract to consumers who may procrastinate canceling it due to naive present-bias. We show that the firm may set a long notice period to exploit naive consumers.
Keywords: D04; D18; D21; D40; D90; L51; 330; notice periods; procrastination; present bias; time inconsistency; consumer naivete